ANALISIS STRATEGI PEMASARAN DIGITAL PADA UMKM KULINER DITINJAU DARI PRINSIP SYARIAH DIKECAMATAN RAWAS ULU - Nadia Anggeraini; Nurlia Fusfita; Eri Nofriza (ICONS: Islamic Economics Journal, 2026)
MSMEs (Micro, Small, and Medium Enterprises) play an important role in the development and economic growth of Indonesia. This role is not only felt in developing countries but also in developed ones. One of the marketing strategies that can be implemented to grow businesses is through digital marketing strategies. The purpose of this study is to examine how digital marketing strategies are applied by MSMEs from the perspective of sharia principles. This research is a descriptive qualitative study, using observation and interview techniques, with 10 informants interviewed. The results show that the digital marketing strategies used by MSME actors in Rawas Ulu District involve the use of social media platforms such as Facebook, Instagram, and WhatsApp. Other digital marketing strategies such as SEO, content marketing, marketing automation, PPC, advertising, and affiliate marketing have not been optimally utilized. MSME actors face limitations in knowledge, access, and capital, as these types of marketing often require paid services. By using social media marketing, MSMEs feel helped in promoting their businesses without incurring significant costs. The implementation of digital marketing strategies clearly facilitates consumer access and provides significant benefits for MSME entrepreneurs.